2019
DOI: 10.1007/s10896-019-00037-3
|View full text |Cite
|
Sign up to set email alerts
|

For Baby’s Sake: Intervention Development and Evaluation Design of a Whole-Family Perinatal Intervention to Break the Cycle of Domestic Abuse

Abstract: For Baby's Sake is an innovative whole-family intervention that works with parents from pregnancy to two years postpartum to break cycles of domestic abuse and improve outcomes for children. The programme launched in 2015 across two community settings in England, with an independent evaluation led by King's College London. This paper aims to (1) summarise the process of developing For Baby's Sake and how it has been embedded within two different settings and (2) describe the evaluation design using early data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…In this mortality study, we highlight the tragic consequences of this gap. There are evidence-based interventions for healing parent and child relationships, 26,35,36 but vulnerable families typically do not have access to such programs in Australia and internationally. 37 No indicators of family socioeconomic status were associated with mortality in the multivariable model (findings consistent with the study by Jackisch et al 16 ) and, as hypothesized, the observed socioeconomic gradient in health is primarily driven by CM history.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In this mortality study, we highlight the tragic consequences of this gap. There are evidence-based interventions for healing parent and child relationships, 26,35,36 but vulnerable families typically do not have access to such programs in Australia and internationally. 37 No indicators of family socioeconomic status were associated with mortality in the multivariable model (findings consistent with the study by Jackisch et al 16 ) and, as hypothesized, the observed socioeconomic gradient in health is primarily driven by CM history.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…This UK‐based whole‐family intervention, developed by the Stefanou Foundation, is aimed at families in the perinatal period where there is identified DVA. The program targets DVA, mental health, parenting, and the parents’ own history of trauma in order to break intergenerational cycles of trauma and abuse (Domoney et al., 2019). Men who engage with For Baby's Sake receive intensive individual therapeutic support from midpregnancy to 2 years postpartum, which encourages acknowledgment of abusive behaviors, provides tools for behavior change and includes exploration of their own traumatic histories.…”
Section: Introductionmentioning
confidence: 99%
“…In South Australia, individuals with a wide range of occupations who interact based support for parents (and parents to be) to create a more nurturing environment for their child, with some programs commencing in pregnancy and continuing through middle childhood. [38][39][40][41] However, many distressed families do not have access to the intensive interdisciplinary and intersectoral family support programs and high-quality therapeutic services that they need.…”
Section: Discussionmentioning
confidence: 99%